Assessment of Inflammatory Markers (C - Reactive Protein and High Sensitivity C-Reactive Protein) in Preeclamptic Pregnant Women in the Third Trimester of Pregnancy - Edebiri O.E.; Akpe C. I.; Adewole A.S.; Okike P.I.; Ehigiamusoe E. A.; Ohiwerei W.O.; Omende K. (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
C-reactive protein (CRP) and high-sensitivity C-reactive protein (hs-CRP) are general marker for inflammation and Arterial damage results from white blood cell invasion. This study aims to assess the level of inflammatory markers C-Reactive Protein (CRP) and High-Sensitivity C-Reactive Protein (hs-CRP) in preeclamptic pregnant women in the third trimester of pregnancy. Fourty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. Blood samples was spun in a bucket centrifuge at 2500 RPM (rounds per minute) for 10 minutes after which plasma was collected and stored frozen in plain sample bottles and was analyzed for C-reactive protein (CRP) and high-sensitivity C-reactive protein (hs-CRP) levels by fluorescence immuno assay. Data obtained from this study were analysed using Graph Pad Prism 9. Results generated were expressed as mean ± SEM and a P-value of ≤ 0.05 were considered statistically significant. The present study showed that there was statistically significant increase in the level of C-Reactive Protein (CRP) and High-Sensitivity C-Reactive Protein (hs-CRP) in preeclamptic women compared to normotensive pregnant women, indicating various underlying pathophysiological processes such as inflammation.